Work–Family Articulation Policies in Portugal and Gender Equality: Advances and Challenges - Susana Ramalho Marques; Sara Falcão Casaca; Manuela Arcanjo (Social Sciences, 2021)
Portugal has been described as a singular case in terms of the participation of women in the labour market and work–life balance policies. Unlike the other so-called Southern European countries, where a belated and somewhat slower move away from the male breadwinner model has been found, Portugal stands out from the other EU member states with its relatively high rate of female employment and the prevalence of the dual-earner model based on continuous and fundamentally full-time employment. Moreover, the “early return to full-time work and a gender equality oriented model” calls for a separate analysis of this country’s case. In addition to providing a comprehensive overview of the singularities of Portugal’s employment patterns and work–family articulation policies, this article substantially adds to the existing literature by bringing new analytical angles to the debate. The intention is therefore to shed light on the political discourses that fuelled the policy debate throughout the three decades following Portugal’s transition to democracy, up until the latest and most decisive policy changes. This article also examines the key social actors’ views about the political process sustaining the development of policies in this area and identifies the major players promoting the most progressive legislative advances in the country.